The effect of phytosulfokine alpha on haploid embryogenesis and gene expression of Brassica napus microspore cultures - Mestinšek Mubi, Špela; Kunej, Urban; Vogrinčič, Valentin; Jakše, Jernej; Murovec, Jana (Frontiers in Plant Science, 2024)
Microspore embryogenesis (ME) is the most powerful tool for creating homozygous lines in plant breeding and molecular biology research. It is still based mainly on the reprogramming of microspores by temperature, osmotic and/or nutrient stress. New compounds are being sought that could increase the efficiency of microspore embryogenesis or even induce the formation of haploid embryos from recalcitrant genotypes. Among these, the mitogenic factor phytosulfokine alpha (PSK-α) is promising due to its broad spectrum of activity in vivo and in vitro. The aim of our study was to investigate the effect of PSK-α on haploid embryogenesis from microspores of oilseed rape (Brassica napus L., DH4079), one of the most important oil crops and a model plant for studying the molecular mechanisms controlling embryo formation. We tested different concentrations (0, 0.01, 0.1 and 1 µM) of the peptide and evaluated its effect on microspore viability and embryo regeneration after four weeks of culture. Our results showed a positive correlation between addition of PSK-α and cultured microspore viability and a positive effect also on the number of developed embryos. The analysis of transcriptomes across three time points (day 0, 2 and 4) with or without PSK-α supplementation (15 RNA libraries in total) unveiled differentially expressed genes pivotal in cell division, microspore embryogenesis, and subsequent regeneration. PCA grouped transcriptomes by RNA sampling time, with the first two principal components explaining 56.8% variability. On day 2 with PSK, 45 genes (15 up- and 30 down-regulated) were differentially expressed when PSK-α was added and their number increased to 304 by day 4 (30 up- and 274 down-regulated). PSK, PSKR, and PSI gene expression analysis revealed dynamic patterns, with PSK2 displaying the highest increase and overall expression during microspore culture at days 2 and 4. Despite some variations, only PSK1 showed significant differential expression upon PSK-α addition. Of 16 ME-related molecular markers, 3 and 15 exhibited significant differential expression in PSK-supplemented cultures at days 2 and 4, respectively. Embryo-specific markers predominantly expressed after 4 days of culture, with higher expression in medium without PSK, while on day 0, numerous sporophyte-specific markers were highly expressed.